Dasatinib-Induced Rhabdomyolysis in a 33-Year-Old Patient with Chronic Myeloid Leukemia. (6th May 2018) - Joel Chandranesan, Andrew Stevenson; Master, Samip; Antosz, Olivia; PeytonThomas, Breanne; Koshy, Nebu
Abstract : Rhabdomyolysis is a life-threatening syndrome due to breakdown of the skeletal muscle. It can be caused by massive trauma and crush injuries or occur as a side effect of medications. Here, we describe a case of a 33-year-old male with human immunodeficiency virus (HIV) and newly diagnosed chronic myeloid leukemia (CML) with severe life-threatening rhabdomyolysis due to a rare offending agent.